Assessment of Anxiety and Depression in Primary Open Angle Glaucoma Patients (A Study of 100 Cases) - Arshad Shaikh, Uzma Fasih, M.Munir Hamirani, Asad Raza Jafri, S Urooj Riaz (Pakistan Journal of Ophthalmology, 2010)
Purpose: The purpose of our study was assessment of anxiety and depression in primary open angle glaucoma patients. Materials and Method: This study was conducted in the Department of Ophthalmology Abbasi Shaheed Hospital from May 2006 to August 2007 in collaboration with Psychiatry Department. Patients who had undergone thorough investigation and examination and diagnosed as patients of primary open angle glaucoma were selected randomly from the glaucoma clinic. These patients were evaluated through Hospital Anxiety and Depression scoring method. It has been translated in Urdu language for better understanding of patients and was filled by the patients themselves. Results: One hundred patients of primary open angle glaucoma were included in our study, 76% percent were male and 24% were female. The average age was 56.21±13.37 years. Anxiety in POAG patients was observed in 33% cases and depression was observed in 24% cases. It is quite obvious that levels of anxiety were high among the patients of primary open angle glaucoma. Conclusion: Large majority of patients with physical disorders including glaucoma suffers from hidden psychiatric disorders that often go undetected. Depression and anxiety constitute greater percentage of this combined psychiatric disorder in physically ill patients. Moreover prevalence of anxiety is more in patients of primary open angle glaucoma as compared to depression.